-13+3x=39+25z

Simple and best practice solution for -13+3x=39+25z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -13+3x=39+25z equation:


Simplifying
-13 + 3x = 39 + 25z

Solving
-13 + 3x = 39 + 25z

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '13' to each side of the equation.
-13 + 13 + 3x = 39 + 13 + 25z

Combine like terms: -13 + 13 = 0
0 + 3x = 39 + 13 + 25z
3x = 39 + 13 + 25z

Combine like terms: 39 + 13 = 52
3x = 52 + 25z

Divide each side by '3'.
x = 17.33333333 + 8.333333333z

Simplifying
x = 17.33333333 + 8.333333333z

See similar equations:

| 2x+7=5x-6 | | 2(3-x)=-4(x-4) | | 5x+3=4x-23 | | 4x+-4=20 | | 7x+1=2x+3 | | 9m+2n-6m+11n= | | 2n+11=41 | | 6x^3+15x= | | 27+32+n=112 | | 15=11x+1 | | 5x/6-13=7 | | 2u+25=7+4u | | 10x-2y=17 | | Iz-2+iI=Iz+3iI | | 4x^2-21x+15=-8+5 | | 15=11x+1+15 | | 19y=-38 | | 3x-8/7=-3 | | x^2+3x+18=-6x-2 | | 26-3X=17 | | x^2+3x-15=7x-3 | | 3tsquard=16t-5 | | 5(x+1)=(2x-4) | | 3x-8/7= | | 3n^2+n-1000=0 | | 6w+4y+9x+6x-12y+5w= | | 6x+3=2x-6 | | 7(2x+1)-4(3x+2)=0 | | 3w+3x-15y+7w+12x+7y= | | 1(x-2)=1(2-x) | | 5x+15+2x-2= | | x^2+34x+68=0 |

Equations solver categories